2019
DOI: 10.1074/jbc.ra118.006468
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic, stem, and transmembrane portions of matriptase-2 are required for suppressing the expression of the iron-regulatory hormone hepcidin

Abstract: Edited by F. Peter Guengerich Matriptase-2 (MT2) is a type-II transmembrane, trypsin-like serine protease that is predominantly expressed in the liver. It is a key suppressor for the expression of hepatic hepcidin, an ironregulatory hormone that is induced via the bone morphogenetic protein signaling pathway. A current model predicts that MT2 suppresses hepcidin expression by cleaving multiple components of the induction pathway. MT2 is synthesized as a zymogen that undergoes autocleavage for activation and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 53 publications
5
14
0
Order By: Relevance
“…Consistent with our previous studies, 9,24 functional analysis revealed that expression of wild-type Mt2 at both doses was able to fully correct the low serum iron and high hepcidin expression status (Figure 1D-E), and it greatly ameliorated the anemia by significantly increasing the levels of hemoglobin, hematocrit, mean cell volume, and mean corpuscular hemoglobin (Table 2). Thus, the transgenic Mt2 acts similarly to the native Mt2.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with our previous studies, 9,24 functional analysis revealed that expression of wild-type Mt2 at both doses was able to fully correct the low serum iron and high hepcidin expression status (Figure 1D-E), and it greatly ameliorated the anemia by significantly increasing the levels of hemoglobin, hematocrit, mean cell volume, and mean corpuscular hemoglobin (Table 2). Thus, the transgenic Mt2 acts similarly to the native Mt2.…”
Section: Resultssupporting
confidence: 90%
“…8,9,23 In vivo studies show that a functional Mt2 requires the transmembrane domain and the entire ectodomain. 24 However, whether Mt2 suppresses hepcidin solely by cleaving Hjv as reported by earlier studies 8,23 remains unknown.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In hepatocytes, it has been well‐documented that inflammation induces hepcidin gene expression via the interleukin‐6 (IL‐6)/signal transducer and activator of transcription 3 (STAT3) pathway, via iron sensing through the transferrin receptor 2 (TfR2)/human hemochromatosis protein (HFE), and the bone morphogenetic protein (BMP)/hemojuvelin (HJV)/SMAD (a small mothers of decapentaplegic protein) pathways, and downregulated by erythroferrone (ERFE) ‐dependent and ‐independent mechanisms . Recent studies have also demonstrated that hepcidin expression can be upregulated by progesterone and mifepristone, two steroid hormones, through cell surface protein progesterone receptor membrane component‐1, transforming growth factor β1, SMAD1/5/8‐independent signaling by activin B, oxidases such as NADPH‐dependent oxidase 4 or artificially overexpressed urate oxidase (UOX), IL‐1β via inducing CCAAT enhancer‐binding protein δ (C/EBPδ) expression, peroxiredoxin‐2 which is a supporter for STAT3 transcriptional activity, fibroblast growth factor‐encoding gene, and downregulated by the immunophilin FKBP12 (FK506‐binding protein 1A) via binding with BMP type I receptor ALK2, cystathionine β‐synthase, TfR1, and matriptase‐2 …”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 99%